A Guide and Tool for Projecting Public Debt and Fiscal Adjustment Paths with Local- and Foreign-Currency Debt - Acosta Ormaechea, Santiago (Technical Notes and Manuals; Technical Notes and Manuals ;, 2021)
This guide presents the analytical underpinnings and a user manual for the Excel-based Public Debt Dynamics Tool (DDT).